A collaborative development initiative to strengthen Midwifery Education in Somalia - Muxamuud, Xabiibo; Mohamed, Fadumo; Khalif Adan, Abdirisak; Saleiman Tukale, Abdikadir; Viberg, Nina; Nor, Hassan; Adem, Rage; Erlandsson, Kerstin; Lindgren, Helena (Somali Health Action Journal, 2024)
Galkayo University, in an ongoing partnership with Benadir University and the Karolinska Institutet, reports on the co-creation of a mentorship program for midwifery educators at Galkayo University. This program was initiated in Spring 2023 with the aim of sharing experiences on midwifery education between educators from Sweden and Somalia—both countries with long traditions of midwifery care. By leveraging the expertise of Swedish and Somali midwifery educators, the mentorship program seeks to bridge gaps in knowledge and skills, ultimately contributing to better midwifery education and care in both Somalia and Sweden. This commentary describes the significance of the program and its potential for impact if scaled up after contextualization.